SAT II. Writing, 1998-99 - Rodman, David; Kaplan Educational Centers (Firm : New York, N.Y.) (New York : Simon & Schuster, 1998)
A guide to getting a higher score on the SAT writing exam that discusses how to prepare for the multiple choice and essay sections, how to maximize test performance, and other related topics.
At head of title: Kaplan.
Adult
Keywords: College entrance achievement tests -- United States; English language -- Composition and exercises -- Examinations -- Study guides; College entrance achievement tests; English language -- Composition and exercises -- Examinations